Bilateral tonic pupils and polyneuropathy in Sjögren's syndrome: a common pathophysiological mechanism? - Waterschoot, M P; Guerit, J M; Lambert, M; de Barsy, T (European neurology, 1991)
One case associating tonic pupils and Sjögren's syndrome is reported. Neurophysiological examination also demonstrated a purely sensory neuropathy. This rare association raises the issue of a common process destroying the ciliary and spinal root ganglia in these patients.